Conversation and Interpreting with Reference to Community, Consecutive, and Simultaneous Interpreting - Safwan Idrees Thanoon (PROSPECTIVE RESEARCHES, 2023)
The present research aims at explaining what interpreting is and its relation to conversation. It sheds light on the types of interpreting, viz, community, consecutive, and simultaneous. A distinction is drawn among interpreters and the characteristics which each carries. It shows that not all the interpreting in a field entitled to him/ her. Competence, practice and other important merits are also tackled in this research in relation to the interpreter's job. We shall try to show that interspersions have to work on one line unless they are highly competent. Interpreters in general should not embark requires a special type of interpreters. We also try to solve some problems faced by interpreters and to ease the difficulty during the work of any interpreter.